DAMPAK PENINGKATAN PAJAK1DAERAH TERHADAP PENDAPATAN9ASLI9DAERAH (PAD) (Survei pada Pemda Kabupaten/Kota Provinsi Jawa Tengah periode 2015-2018) - Prabowo, Elsa Putri (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2022)
The purpose of this research is to knowing the impact of advertisement tax, parking tax, and restaurant tax on regional original revenue(PAD). The sample of research was taken by purposive sampling technique. Observed in this research are 76 records out of 19 district/city in Province of Central Java. Kind of the research used is panel regression with E-views 11. Advertisement tax, parking tax, and restaurant tax has negative not significant on regional original revenue. Keyword: Advertisement Tax, Parking Tax, Restaurant Tax, Regional Original Revenue.